The Starting School Study: Mothers' Perspectives of Transition to School. Issue 4 (December 2017) - Kaplun, Cathy; Dockett, Sue; Perry, Bob
THE STARTING SCHOOL STUDY explored the transition to school from the perspectives of parents living in a disadvantaged area of Sydney, Australia. Fifty-seven parents participated in semi-structured interviews about their child's transition to school between 2009 and 2011. Topics discussed included: preparation for school, the first day, school relationships, supports and barriers to involvement and aspirations. A team of researchers working collaboratively in 2011 consolidated national and international research and theory of transition to school, to develop and publish an aspirational document entitled Transition to school: Position statement. The statement recognised and promoted the importance of transition to school using four constructs: opportunities, expectations, entitlements and aspirations. The results of the Starting School Study are discussed using these constructs. Overall, mothers in the study valued education, wanted their children to achieve and be successful, and hoped their children would have positive experiences of school; better than their own. The pivotal role of the teacher is discussed.